2017
DOI: 10.29252/nrip.ptj.7.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Level Laser Therapy on Pain and Range of Motion of Patients With Knee Osteoarthritis

Abstract: Purpose: Osteoarthritis is one the most common chronic diseases of the joints that mostly affects knee joint. Low power laser is one the minimally invasive treatments of osteoarthritis. However, the efficacy of this therapy is still controversial. This study aimed to evaluate the efficacy of low power laser therapy in reducing pain and increasing knee range of motion compared to placebo laser. Methods:This study was a double-blind clinical trial performed at a day clinic in Tehran, Iran, from March 2016 to Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The present study aimed to compare two common conservative treatments (orthosis and physical therapy) on pain and function in individuals with knee OA. Orthoses and physical therapy are the most common conservative managements of knee OA that are effective in reducing pain and improving function 13,18 . Comparing the two interventions in the present study, the results demonstrated that the orthosis group (using both knee brace and LWLs) had better results for pain score related to VAS than the physical therapy group immediately after and 6 weeks of using the intervention, with a significant difference between the two groups.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The present study aimed to compare two common conservative treatments (orthosis and physical therapy) on pain and function in individuals with knee OA. Orthoses and physical therapy are the most common conservative managements of knee OA that are effective in reducing pain and improving function 13,18 . Comparing the two interventions in the present study, the results demonstrated that the orthosis group (using both knee brace and LWLs) had better results for pain score related to VAS than the physical therapy group immediately after and 6 weeks of using the intervention, with a significant difference between the two groups.…”
Section: Resultsmentioning
confidence: 54%
“…Orthoses and physical therapy are the most common conservative managements of knee OA that are effective in reducing pain and improving function. 13,18 Comparing the two interventions in the present study, the results demonstrated that the orthosis group (using both knee brace and LWLs) had better results for pain score related to VAS than the physical therapy group immediately after and 6 weeks of using the intervention, with a significant difference between the two groups. A recent systematic review stated that, because lower-limb joints are linked as a closed chain, ankle and knee joints are considered as an integral unit in the human body.…”
Section: Discussionmentioning
confidence: 61%
“…To date, we have located a total of twenty-five studies of LLLT for KOA or knee pain, seventeen of which were not cited in the Guideline though were available up to 2018 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. One study has not been considered as it was a study using laser acupuncture, though had been included in several of the systematic reviews [36].…”
Section: Literature Review Of the Guidelinementioning
confidence: 99%
“…Of these, there were seven double-blind randomised studies comparing LLLT with placebo (sham laser) [19][20][21][22][23][24]35]. Of these seven studies, five demonstrated both clinically and statistically significant results favouring LLLT.…”
Section: Literature Review Of the Guidelinementioning
confidence: 99%